Brittle Materials and Stress Concentrations: are they Able to withstand?. (2015) - Sapora, Alberto; Cornetti, Pietro; Carpinteri, Alberto; Firrao, Donato
Abstract: The combination of brittleness in materials and stress concentrations may lead to premature fracture of structural components. To improve the modelling capability more and more sophisticated methods have to be employed. To the purpose a Finite Fracture Mechanics (FFM) criterion based on the contemporaneous fulfilment of a stress requirement and the energy balance has been proposed in the literature. This coupled approach is here refined and applied to investigate brittle fracture in rounded V-notched samples under mode I loading. The failure FFM condition is expressed by a system of two equations in two unknowns: the critical crack advance and the apparent generalized fracture toughness (i.e., the failure load). The refined criterion is validated by its implementation with various experimental data, available in the literature, related to ceramic, metallic, and plastic brittle materials.